Statin versus no statin after treatment with pipeline embolization device for intracranial aneurysms: a meta-analysis - Barbosa, Nathalia Soares; Gouhie, Felipe Araujo; Hakkeem, Bezalel; Machado, Amanda; Telles, João Paulo Mota; Soares, Luís Gustavo Biondi; Barbosa, Leandro de Assis (Arquivos de Neuro-Psiquiatria, 2025)
Some studies demonstrated the role of statin therapy in improving outcomes after coil embolization or surgical clipping of cerebral aneurysm. However, the benefit of statins after pipeline embolization device (PED) for intracranial aneurysms is not well established.To evaluate the effects of statins on hemorrhagic and ischemic complications as well as on complete occlusion of aneurysm in the treatment with PED.We searched the PubMed, Embase, and Cochrane Library databases for articles published from their inception to November 2024. Data were collected from observational studies comparing statin to no statin therapy following pipeline embolization.Four studies were included, comprising 2,822 patients and 3,063 aneurysms, 127 of which were ruptured and 4 of which received adjunctive coil embolization. Total hemorrhagic complication was reduced in the statin group (risk ratio [RR] = 0.50; 95%CI: 0.29–0.85; p = 0.010; I2 = 0%) but did not reveal difference in restricted propensity score-matched (PSM) analysis (RR= 0.50; 95%CI: 0.24–1.07 p = 0.073; I2 = 27%). There was no difference between the groups in complete occlusion of aneurysm rate at the last follow-up (RR = 0.94; 95%CI: 0.88–1.00; p = 0.055; I2 = 8.0%) or total ischemic complications (RR = 1.48; 95%CI: 1.06–2.07; p = 0.021; I2 = 0%).Statin use significantly reduced hemorrhagic complications after PED; however, this result should be interpreted cautiously due to study limitations. No significant differences were noted in complete occlusion rates or ischemic complications between the groups.
Keywords: Embolization, Therapeutic; Stents; Intracranial Aneurysm; Hydroxymethylglutaryl-CoA Reductase Inhibitors